The Influence of Transformational Leadership and Job Satisfaction mediated by Work Motivation on the Performance of Functional and Structural Officials of the Mappi District Education Office - Wen, Geradus; Kambu, Arius Andreas; Ikhwan, Ikhwan (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The main problem of this study is that the performance of functional and structural staff of the education office has not reached the expected target so that the purpose of this study is to analyze the effect of transformational leadership and job satisfaction with work motivation as a mediating variable.The sampling technique used accidental sampling technique with a sample size of 100 respondents. The variable measurement was carried out using Likert scale parameters. Data analysis using descriptive statistics using SEM- PLS to test the hypothesis. The results showed that leadership transformation and job satisfaction had a significant effect on performance through work motivation, while the direct test results showed that transformational leadership and job satisfaction had no effect on performance. The results of this test also confirm that transformation leadership and job satisfaction affect work motivation and work motivation affects performance.